2017
DOI: 10.4046/trd.2017.80.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and the Risk of Rheumatoid Arthritis: An Insight into the Heterogeneity and Phenotypes of Asthma

Abstract: Asthma is traditionally regarded as a chronic airway disease, and recent literature proves its heterogeneity, based on distinctive clusters or phenotypes of asthma. In defining such asthma clusters, the nature of comorbidity among patients with asthma is poorly understood, by assuming no causal relationship between asthma and other comorbid conditions, including both communicable and noncommunicable diseases. However, emerging evidence suggests that the status of asthma significantly affects the increased susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 158 publications
0
17
0
Order By: Relevance
“…However, we did not find all expected connections, especially for drugs for cardiovascular diseases, probably because of their wide range of use and the rather high socioeconomic status of our population of elderly women [31]. Interestingly, our study supports the relationship between asthma and rheumatism/inflammation, which might have some implications in the management of these patients by considering leukotriene receptor antagonists as a therapeutic option [32].…”
Section: Discussionmentioning
confidence: 51%
“…However, we did not find all expected connections, especially for drugs for cardiovascular diseases, probably because of their wide range of use and the rather high socioeconomic status of our population of elderly women [31]. Interestingly, our study supports the relationship between asthma and rheumatism/inflammation, which might have some implications in the management of these patients by considering leukotriene receptor antagonists as a therapeutic option [32].…”
Section: Discussionmentioning
confidence: 51%
“…The co-existence of asthma with chronic obstructive pulmonary disease may also partly explain the association between asthma and diabetes and mental disorders. Asthma has also been shown to be a risk factor of developing rheumatoid arthritis (42), but more studies are needed to explore its association with osteoarthritis. The relationships of osteoarthritis with cardiometabolic and mental disorders have been observed in many studies (28,43), but the association between osteoarthritis and cancer is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to positive association, a Finnish cohort study has indicated that the cumulative incidence of asthma in children with coeliac disease or RA was significantly higher than in children without coeliac disease or RA, concluding that Th1 and Th2 diseases could indeed coexist [ 16 ]. Furthermore, a review on the relationship between asthma and RA [ 17 ] and a study between asthma and proinflammatory conditions [ 18 ], done by the Mayo Medical School of Rochester, USA, pointed out that although a population-based cohort study is required utilizing a well-defined population, the standing evidence from these studies found through the review is quite convincing and strongly supports the positive association between asthma and the risk of RA. Conversely, a study done in Germany stated an opposing result supporting that there exists an inverse association between Th1 and Th2 diseases, where RA and atopy antagonize each other and that a change in the cytokine patterns of Th1 and Th2 cells could provide an indication for curative effect on RA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested few potential mechanisms underlying the positive association present between respiratory allergic diseases and the increased risk of prevalence of RA [ 17 ]. Possible mechanisms are genetic, environmental factors, natural killer group 2D (NKG2D), and tumor necrosis factor alpha (TNF-alpha).…”
Section: Discussionmentioning
confidence: 99%